„…wobec rozmiarów Zagłady świat doświadczył ogromnej winy…”. Debaty wokół nauczania o Holokauście - Ambrosewicz-Jacobs, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
In Europe a strong association with a sense of victimhood based on the memory of terror and murder in many cases creates conflicting approaches and generates obstacles to providing education about Jewish victims. Suppressed shame and tension together with conflicts related to insufficiently acknowledged victimhood of one’s own group intersect with political agreements on teaching about the Shoah such as the signing of the Stockholm Declaration and membership in the IHRA and other IGOs. The text presents selected challenges and the dynamics of education about the Holocaust and poses questions such as whether it is possible to identify clear concepts, strategies and good educational practices, whether there are links between education about the Holocaust, education against genocides and human rights education, and how education about the Holocaust relates to attitudes toward Jews? In many European countries disparities have grown between Holocaust research and education about the Holocaust. Empirical studies in the field of education reveal that there is a gap between research and education in some aspects of the way the Holocaust is presented, particularly with regard to the attitudes of local populations towards Jews during the Shoah. Nevertheless, the number of educational initiatives designed to teach and learn about the Shoah is steadily increasing.
Keywords: Holokaust; całkowita zagłada; nauczanie; historia; polityka historyczna; postkomunizm